Peningkatan Profitabilitas Dan Free Cash Flow Terhadap Kebijakan Dividen - Melly Azahra Agustin; Lidya Martha (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This study aims to see the effect of profitability proxied by return on assets and free cash flow on dividend policy in companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 – 2021. With a population of 810 companies, a sample of 32 companies was obtained using purposive sampling technique. The research method used in this research is quantitative. The data analysis technique uses panel data regression analysis with the regression model used is the fixed effect model which is processed with Eviews8 software. Based on the results of data analysis that has been carried out using hypothesis testing (t-test), proving that the profitability ratio proxied by return on assets has a significant effect on dividend policy, and the free cash flow variable has no significant effect on dividend policy in listed companies on the IDX.